POTENSI LIMBAH KELAPA SAWIT SEBAGAI PAKAN TERNAK RUMINANSIA DI KECAMATAN BULIK KABUPATEN LAMANDAU - Firdaus Husein Situmorang; Dwi Yuzaria; Muhammad Amran; Monasdir Monasdir; Riskayanti Riskayanti; Lailatun Nisfimawardah (Jurnal Agriovet, 2025)
This study aims to identify the potential of palm oil waste as ruminant livestock feed in Bulik District, Lamandau Regency. The research method used is a survey method using a questionnaire. The sample used was 60 farmers determined using the Slovin formula. The variables observed were the potential of palm oil waste as livestock feed consisting of fronds and leaves and technical aspects of livestock maintenance. Data analysis was descriptively based on the Technical Factor Identification Score of Livestock Standard Guidelines from the Directorate General of Livestock (1990). The results showed that the potential for palm oil fronds and leaves waste for feed was: 87.657.600 kg for each year and could feed 6,419,65 AU. The technical aspects of beef cattle farming in Bulik District were: 53.41% with categories: 51.04% livestock; 46.90% feed, 62% maintenance, 81.11% housing and 40.88% healthy technical aspects.